Model Komunikasi Persuasif Pada Pengikut Akun Instagram @infogarut Dalam Pemberitaan Citizen Journalism - Salsabila, Gina; Salamah, Ummu; Nurhadi, Zikri Fachrul (Universitas Prof. Dr. Moestopo (Beragama), 2024)
Social media as an interactive platform for citizen journalism is increasingly important in the growing internet era. The focus of the research is the Instagram account @infogarut, as a citizen journalism platform in Garut. The purpose of this research is to find out how persuasive communication on @infogarut account followers related to citizen journalism news in the central route and peripheral route. This research method uses descriptive method with qualitative approach. The theory used is persuasive communication theory with the Elaboration Likelihood Model (ELM) model. Data collection techniques were carried out through interviews, observation of literature study and documentation. The results showed that the central route creates respondents who are involved and check facts and analyze information in depth before forming an opinion or taking action. The peripheral route in turn creates respondents who are more passive readers and only receive information without detailed analysis. The @infogarut account is known for providing the latest facts and information about Garut. This study provides insight into how citizen journalism on social media, especially Instagram, can influence the way people interact and react to information.